Kardiochirurgia DorosłychAblation as a valuable supplementation of mitral valve operations – in our material - Jurko, Cezary; Krawczyk, Elzbieta; Stążka, Janusz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2007)
The article presents the author’s experience with 30 endocardial radiofrequency ablations done at the Department of Cardiac Surgery of the Medical University of Lublin. Paroxysmal or permanent atrial fibrillation were indications for the operation. Ablation was done during mitral valve surgery. No complications after the ablation were observed. Recurrence of paroxysmal atrial fibrillation in 77% of patients was noticed after the operation. Seventy percent of patients required electrical cardioversion. Sinus rhythm was observed in 70% of patients at discharge and in 83% after a year. In our opinion ablation is a valuable supplementation of mitral valve surgery.